A Psychometric Examination of a Modified Eight-Item Version of the Children’s Eating Disorder Examination - Jongenelis, Michelle; Byrne, S.; Pettigrew, Simone; Allen, K.; Watt, F. (American Psychological Association, 2014)
Eating and body image disturbances in children are typically assessed using the Children’s Eating Disorder Examination (ChEDE); however, support for the reliability and validity of scores on this measure is mixed. Furthermore, previous studies suggest that scores obtained from a simplified 8-item version of the ChEDE may be more reliable and useful for research purposes than scores obtained from the full scale. The present study sought to psychometrically evaluate the reliability and factor structure of this brief 8-item scale. Two separate community-based samples of 6- to 11-year-olds (N = 535) were administered the ChEDE as part of a broader assessment battery. The brief 8-item model provided a good fit to the data, as determined by confirmatory factor analysis. Additionally, scores obtained from the 8-item scale, as well as a global ChEDE score, provided reliable measures of a child’s eating disorder symptoms, and were superior to the original 4 subscales in both healthy-weight and overweight/obese samples. The brief 8-item scale may therefore be used by researchers who want a reliable and valid index of global eating disorder psychopathology without doing a full interview.